Drivers of Credit Cards Adoption and Usage: An Exploratory Study - Chong, Seow Fun (2009)
The competition among different credit card issuers has become more intense, leading to increased challenge for market growth opportunities in terms of credit cards circulation and share of wallet in terms of credit card usage. In response to competition from existing players and possible new entrants to the credit card market, credit card issuers need to be creative and innovative in their marketing strategies to gain competitive advantage. It is crucial for marketing practitioners in the credit card industry to gain an in-depth understanding of customers’ attitude towards credit cards in relation to the drivers of credit cards adoption and usage. This study is exploratory in nature using qualitative method which aimed to examine the drivers of credit card adoption usage. The findings of this study indicate various product attributes, branding and service quality elements that are salient features in driving credit cards adoption and usage. Marketing theories related to customer behaviour, branding perspectives and customer satisfaction will form part of the literature review for this study.